O (re) conhecimento da vontade de potência dos educadores pela narração de suas histórias de vida - Machado, Alexsandro dos Santos (2005)
This work shows a methodology of analysis about will of educators power through narration of their history of life. So that, three educators with great teaching experience were interviewed, leaving them free to tell their trajectories how they wanted. To consider each narrative like a singular masterpiece, the author exhibits the power of life of each interviewee, drawing a parallel of narratives with literary genders. Through the complex of plot that consists each educator s life threads are handled among various areas of knowledge, so everybody involved in the process of this paper interviewees, researcher, academy, schools - find in it a space to (re) creation and (re) knowledge of new possibilities of life in Education.